2003
DOI: 10.1091/mbc.e02-10-0637
|View full text |Cite
|
Sign up to set email alerts
|

Lens Connexins α3Cx46 and α8Cx50 Interact with Zonula Occludens Protein-1 (ZO-1)

Abstract: Connexin alpha1Cx43 has previously been shown to bind to the PDZ domain-containing protein ZO-1. The similarity of the carboxyl termini of this connexin and the lens fiber connexins alpha3Cx46 and alpha8Cx50 suggested that these connexins may also interact with ZO-1. ZO-1 was shown to be highly expressed in mouse lenses. Colocalization of ZO-1 with alpha3Cx46 and alpha8Cx50 connexins in fiber cells was demonstrated by immunofluorescence and by fracture-labeling electron microscopy but showed regional variation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
94
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(97 citation statements)
references
References 52 publications
1
94
2
Order By: Relevance
“…To examine whether alterations in lens fiber cell shape were caused by changes in cell-cell interactions, P21 lenses were analyzed for changes in gap and adherens junctions. Gap junctions were detected using antibodies against either Cx46 or the Cx46 interacting protein ZO-1 (26). In P21 WT lenses, the majority of the gap junctions were located on the broad side of the fiber cell hexagonal profile as previously reported (15,26).…”
Section: Resultsmentioning
confidence: 53%
“…To examine whether alterations in lens fiber cell shape were caused by changes in cell-cell interactions, P21 lenses were analyzed for changes in gap and adherens junctions. Gap junctions were detected using antibodies against either Cx46 or the Cx46 interacting protein ZO-1 (26). In P21 WT lenses, the majority of the gap junctions were located on the broad side of the fiber cell hexagonal profile as previously reported (15,26).…”
Section: Resultsmentioning
confidence: 53%
“…Despite the growing number of Cxs reported to interact with ZO-1, including Cx43, Cx45, Cx31.9, Cx46, Cx50 (Giepmans and Moolenaar, 1998;Toyofuku et al, 1998;Kausalya et al, 2001;Laing et al, 2001;Nielsen et al, 2002Nielsen et al, , 2003, the function of this interaction and the significance of the differential binding of these Cxs to the second PDZ domain compared with the binding of Cx36 to the first PDZ domain of ZO-1 (Li et al, 2004) remains to be determined. Nevertheless, the importance of Cx47/ZO-1 interaction is suggested by the multifunctional, signaling and/or scaffolding role of ZO-1 in other cell types (Mitic and Anderson, 1998;Thomas et al, 2002;Gonzalez-Mariscal et al, 2003 7).…”
Section: Cx47 Association With Zo-1mentioning
confidence: 99%
“…In addition to containing multiple Cxs, it is now recognized that gap junctions in a variety of systems are associated with regulatory or structural proteins, and it has been reported that the c-terminus of a number of Cxs, including Cx43, Cx31.9, Cx45, Cx46 and Cx50, interact with the postsynaptic protein PSD95/Drosophila junction protein Disc-large/tight junction protein zonula occludens-1 (ZO-1) (Giepmans and Moolenaar, 1998;Toyofuku et al, 1998;Kausalya et al, 2001;Laing et al, 2001;Nielsen et al, 2002Nielsen et al, , 2003. Sequence similarities between the c-terminus of Cx47 and the PDZ-binding consensus motifs in these other Cxs suggest that it may also interact with ZO-1.…”
mentioning
confidence: 99%
“…Three pGEX-3X plasmids each containing one of the three GST-linked PDZ domains of ZO-1 (Nielsen et al, 2002(Nielsen et al, , 2003 were kindly provided to us by Dr. B. Giepmans (University of California, San Diego, CA, USA). Preparation of GST-PDZ fusion proteins from these plasmids expressed in Escherichia coli DH5α and binding of fusion proteins to glutathioneagarose beads has been previously described (Li et al, 2004).…”
Section: Gst-pdz Domain Fusion Proteins and In Vitro Pull-down Assaysmentioning
confidence: 99%
“…Moreover, while Cx47 was earlier reported to be expressed in neurons (Teubner et al, 2001) and more recently has been described as a myelin-related gene (Menichella et al, 2003), our initial observations indicated Cx47 targeting primarily to oligodendrocyte cell bodies, and only sparse association with myelin (Nagy et al, 2003b(Nagy et al, , 2004. Thus, the cellular and subcellular expression patterns of Cx47 and the localization and ultrastructural relationships of Cx47 to other glial Cxs in the CNS remain to be clarified.In addition to containing multiple Cxs, it is now recognized that gap junctions in a variety of systems are associated with regulatory or structural proteins, and it has been reported that the c-terminus of a number of Cxs, including Cx43, Cx31.9, Cx45, Cx46 and Cx50, interact with the postsynaptic protein PSD95/Drosophila junction protein Disc-large/tight junction protein zonula occludens-1 (ZO-1) (Giepmans and Moolenaar, 1998;Toyofuku et al, 1998;Kausalya et al, 2001;Laing et al, 2001;Nielsen et al, 2002Nielsen et al, , 2003. Sequence similarities between the c-terminus of Cx47 and the PDZ-binding consensus motifs in these other Cxs suggest that it may also interact with ZO-1.…”
mentioning
confidence: 99%